Helping poorer countries make locally informed health decisions. (16th July 2010) - Chalkidou, Kalipso; Levine, Ruth; Dillon, Andrew
Abstract : Health spending in low income countries is too often driven by outside pressure rather than local evidence. Kalipso Chalkidou, Ruth Levine, and Andrew Dillon report on efforts to help them match spending to local needs